PENERAPAN MODEL PEMBELAJARAN PJBL BERBANTUAN MEDIA KOPIKEGAYA UNTUK MENINGKATKAN HASIL BELAJAR IPAS KELAS IV SD MUHAMMADIYAH BIRRUL WALIDAIN KUDUS - AMALIA, LAILA ILMIYATUL; RONDLI, WAWAN SHOKIB; ISMAYA, ERIK ADITIA (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2024)
This research aims to analyze the improvement in learning outcomes of fourth grade students at SD Muhammadiyah Birrul Walidain Kudus for the 2023/2024 academic year in the science and sciences subject by applying the Project Based Learning learning model assisted by KOPIKEGAYA media. This research uses the Classroom Action Research (PTK) method which is carried out in two cycles with four stages, namely planning, implementation, observation and reflection in each cycle. Participants in this research were 27 grade IV students at SD Muhammadiyah Birrul Walidain Kudus, with details of 16 male students and 11 female students. Data collection methods such as interviews, observation, tests and documentation were used in this research. The knowledge domain learning results from cycle I obtained a classical level of 55.55%, then in cycle II it increased to 77.77%. In cycle I there was an increase in learning outcomes in the affective domain (attitude) with an average score of 71.66%, cycle II increased to 82.77%. Learning outcomes in the psychomotor domain (skills) increased from cycle I, obtaining an average score of 72.52%, then increased in cycle II, which obtained an average score of 84.64%. Therefore, it can be concluded that the application of the Project Based Learning learning model assisted by KOPIKEGAYA media can improve the science and science learning outcomes of fourth grade elementary school students. ABSTRAKPenelitian ini bertujuan untuk menganalisis peningkatan hasil belajar siswa kelas IV SD Muhammadiyah Birrul Walidain Kudus tahun pelajaran 2023/2024 pada mata pelajaran IPAS dengan menerapkan model pembelajaran Project Based Learning berbantuan media KOPIKEGAYA. Penelitian ini menggunakan metode Penelitian Tindakan Kelas (PTK) yang dilaksanakan dalam dua siklus dengan empat tahap yaitu perencanaan, pelaksanaan, observasi, dan refleksi pada setiap siklusnya. Partisipan dalam penelitian ini adalah siswa kelas IV SD Muhammadiyah Birrul Walidain Kudus yang berjumlah 27 siswa, dengan rincian laki-laki 16 siswa dan perempuan 11 siswa. Metode pengumpulan data seperti wawancara, observasi, tes, dan dokumentasi digunakan dalam penelitian ini. Hasil pembelajaran ranah pengetahuan dari siklus I memperoleh tingkat klasikal sebesar 55,55%, kemudian pada siklus II meningkat menjadi 77,77%. Pada siklus I terjadi peningkatan hasil belajar ranah afektif (sikap) dengan rata-rata skor 71,66% siklus II mengalami peningkatan menjadi 82,77%. Hasil belajar ranah psikomotorik (keterampilan) mengalami peningkatan dari siklus I memperoleh nilai rata-rata sebesar 72,52% kemudian meningkat pada siklus II yang memperoleh nilai rata-rata 84,64%. Maka dari itu ditarik kesimpulan bahwa penerapan model pembelajaran Project Based Learning berbantuan media KOPIKEGAYA dapat meningkatkan hasil belajar IPAS siswa kelas IV SD.